Psychometric Properties of the Smartphone Overdependence Scale among Indonesian Adolescents - Samudera, Arung; Zaskia Qonita Cayyira; Shefira Ramadani; Nabila Salima; Luthfiyah Nursyifa; Gina Meilina; M. Mifta Hulfi Fikri; M. Raihan Hidayat A. (ANFUSINA: Journal of Psychology, 2025)
The increasing use of smartphones among adolescents has the potemtial to lead to exercise dependence (smartphone overdependence) which has negative impacts. Therefore, a valid and reliable adaptive measurement instrument is needed. This study aims to test the psychometric properties of the Indonesia version of the Smartphone Overdependence Scale (SOS). This study involved 245 Indonesian adolescents (aged 13-21 years) selected using a convenience sampling technique. Data analysis used Confirmatory Factor Analysis (CFA) to test the three-factor structure of the model and the Rasch Model to prove the functionality of the statement items. The CFA analysis confirmed that the three-factor model had excellent model fit (CFI = 0,992; TLI = 0,989;  RMSEA = 0,035). The factor loading values for all items were 0,489-0,845 with high internal consistency. The Rasch Model approach met the assumptions of unidimensionality (45,7%) and local independence. The evaluation showed that 9 of the 10 items functioned well, except for item 9 (outfit MNSQ = 1,61), which required revision. The Wright-Maps analysis indicated that this instrument lacks sensitivity for detecting very extreme levels of dependency. The Indonesian version of the SOS has valid and reliable psychometric properties, making it suitable for use by counselors and mental health practitioners to detect the risk of technology dependency in adolescents. Keywords:   Ketergantungan smartphone, adaptasi instrumen, CFA, Rasch Model dan Remaja